Social Constructionism Turned Into Human Service Work - Järvinen, Margaretha; Miller, Gale (Qualitative Sociology Review, 2015)
Studies of applied constructionism are opportunities for scholars to explore how social constructionism is a resource used by claims-makers in describing and justifying their orientations to professional practice. The present paper expands sociological constructionism by analyzing applied constructionism in social problems work in Copenhagen, Denmark. Based on interviews with staff members in narrative drug treatment, we explore two themes: the relationship between dominant and liberating narratives and the position of expert knowledge in narrative therapy. Our guiding framework is Ian Hacking’s inquiry into the Social Construction of What? and Kenneth Burke’s dialogic approach of comparing statements to counterstatements. The purpose of the paper is to link academic studies of the social construction of realities to applied constructionists’ principles in addressing social problems. We do this by describing narrative therapists’ critical reflections on their own work, suggesting that these reflections are not only useful when it comes to developing narrative therapy but also for the advancement of academic constructionism.